Permeability Reduction and Electrochemical Impedance of Fractured Rock Grouted by Microbial-Induced Calcite Precipitation - Shuquan Peng; Kejia Zhang; Ling Fan; Jingyu Kang; Kang Peng; Fan Wang (Geofluids)
The poor impermeability of fractured rock induced by excavation and construction is improved through the application of microbial-induced calcite precipitation (MICP), but it is difficult to monitor and evaluate the permeability reduction under a confining pressure and fracture aperture. For this, the grouting ratio, permeability, and electrochemical impedance of fractured rock with MICP grouting were experimented with, considering the effects of fracture aperture and confining pressure. The equivalent circuit model of grouting-fractured rock is presented, and the corresponding ratio of the electrical resistivity and cross-sectional area of the grouted fracture (ρ/S) is indicated by an electrochemical impedance spectroscope (EIS). The relationships of the permeability coefficient, the ρ/S, and the grouting ratio are analysed. The experimental results show that the Darcy permeability coefficient of fractured rock with MICP grouting is reduced by an order of magnitude of 3 to 4. As fracture aperture ranged from 1.28 to 2.56 mm and grouting rate was 0.003 ml/s, the Darcy permeability coefficient decreased with an increase in confining pressure. The grouting ratio and fracture aperture also decreased with a reduction in ρ/S. The results also showed that the permeability reduction of MICP correspondingly increased in these conditions. What is more, the Darcy permeability coefficient of fractured rock grouted by MICP and its permeability reduction may be well predicted by confining pressure and ρ/S. This study provides a new EIS method for predicting the reduction in permeability of MICP grouting-fractured rock and further enriches the application of MICP and EIS techniques in impermeable rock engineering.